The Geomorphological Development of Badra Alluvial Fan - هالة محمد عبد الرحمن (College of Education for Women, 2019)
The geomorphological importance of studying the alluvial fan derives from the fact that in enables us to know the Origin and development of such a phenomenon which cover a vast area in different regions. This study tackles the geomorphological development of Badra alluvial fan through knowing the factors of its origin, development, form and their present area, by using the climate hydrological In formation besides using topographic Maps and changes detection for different years (1973 - 2013) from satellite images